Green and Sustainable Infrastructure Construction Materials - Wang, Jiaqing; Guo, Shuaicheng; Si, Ruizhe; Liu, Chaochao; Gong, Fangyuan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As people become more environmentally aware and recycle , the reuse of waste materials and the application of sustainable techniques in the construction field have become popular. This reprint collates new green and sustainable infrastructure construction materials, including cement and asphalt concrete, biomass, and composite infrastructure materials. This collection should be used as a guidance for the future field application of new techniques for the improved environmental sustainability of infrastructure constructions.